Impact of belief and Cognitive similarity in the innovation process at Hanoi Telecom Joint Stock Company = Tác động của niềm tin và sự tương đồng nhận thức trong quá trình đổi mới sáng tạo tại Công ty Cổ phần Viễn thông Hà Nội - Hoàng, Tạ Quang (2020)
The thesis assesses the impacts of beliefs and Cognitive similarity in the innovation process of employees in Hanoi Telecom Company. Considering the impact of these factors on the knowlege sharing in the whole company. The factors will help employees closer together, encourage sharing their knowledge and experience to others in the company. From the sharing of knowledge, the process of innovation will be carried on from inside. The research method used questionnaires and stactic softwares to figure out the impact levels of the two factors 'Belief' and the’’ Cognitive similarity’’